2021
DOI: 10.1186/s12929-021-00750-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of transition zone prostate cancer by multiparametric MRI: added value of MR spectroscopic imaging with sLASER volume selection

Abstract: Background Current multiparametric MRI (mp-MRI) in routine clinical practice has poor-to-moderate diagnostic performance for transition zone prostate cancer. The aim of this study was to evaluate the potential diagnostic performance of novel 1H magnetic resonance spectroscopic imaging (MRSI) using a semi-localized adiabatic selective refocusing (sLASER) sequence with gradient offset independent adiabaticity (GOIA) pulses in addition to the routine mp-MRI, including T2-weighted imaging (T2WI), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The loss in SNR by performing MRSI at 3T with a phased array coil combination instead of an ERC can be mitigated using LASER type of acquisition sequences [ 17 , 28 , 96 ]. Several studies have demonstrated that in this way MRSI of the prostate can be performed reliably within acceptable time in clinical routine [ 28 , 82 , 106 , 111 ].…”
Section: Hardwarementioning
confidence: 99%
See 3 more Smart Citations
“…The loss in SNR by performing MRSI at 3T with a phased array coil combination instead of an ERC can be mitigated using LASER type of acquisition sequences [ 17 , 28 , 96 ]. Several studies have demonstrated that in this way MRSI of the prostate can be performed reliably within acceptable time in clinical routine [ 28 , 82 , 106 , 111 ].…”
Section: Hardwarementioning
confidence: 99%
“…The MR investigations were performed at 3 T with a phased array coil for signal reception. For details see [ 111 ]. A Transversal T2 w MRI shows at least two locations with low signal intensity suspicious for cancer in the left and right side of the transition zone (TZ) of the prostate (white arrows).…”
Section: Processing and Interpretation Of 1 H Mrsi...mentioning
confidence: 99%
See 2 more Smart Citations
“…This loss of the citrate-secretory phenotype occurs in virtually all PCa cases, highlighting it as a hallmark of PCa [ [1] , [2] , [3] , [4] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ]. Accordingly, decreases in prostate citrate levels can be detected using magnetic resonance spectroscopy, and several studies have identified this decrease in citrate as a biomarker for PCa diagnosis [ [16] , [17] , [18] ]. Moreover, lower intratumor citrate concentrations have been associated with shorter recurrence-free survival, suggesting that reprogramming of citrate is not only linked to carcinogenesis but also to PCa progression [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%